An evaluation of the role played by the Civil Service Commission in promoting sound employment relations in Zimbabwe’s Public sector: The case of the Ministry of Primary and Secondary Education Mutare District from 2012 to 2016. - Makamure, Vimbai (Midlands State University, 2020)
A Civil Service Commission (CSC) is an agency that is backed by legislature to regulate the employment and working conditions of civil servants. The Civil Service Commission of Zimbabwe formally named the Public Service Commission (PSC) under the Lancaster House Constitution of 1979. Zigora and Chigwamba (2000) has it that, the Public Service Commission was established by an Act of Parliament (Public Service Act 1995) in accordance with Sections 73, 74 and 75 of the Constitution of Zimbabwe. The Public Sector in Zimbabwe has been characterised by ethical crisis and deficient trends that involve corruption, boyism politics, laziness and nepotism resulting in lack of sound employment relations. This has necessitated the reform of government’s central human resource management agency, the Civil Service Commission, aimed at promoting corporate governance and protecting the administrative principles within management circles of the state parastatals. The research explored the functions of the CSC and the challenges it is facing in the promotion of sound employment relations in Zimbabwe’s educational sector. Allan Fox (1966) explained the theoretical approaches to employment relations which comprise of, unitary theory and pluralist theory. The researcher did comparative analysis looking into other countries who are enhances for the promotion of good employment relations, these countries include; South Africa, Malaysia and UK. The research’s case study is Zimbabwe’s Ministry of Primary and Secondary Education,